Reflecting on Hybrid Events: Learning from a Year of Hybrid Experiences - Ansah, Alberta A; Zhong, Sailin; Vivacqua, Adriana S; Boll, Susanne; Constantinides, Marios; Verma, Himanshu; Ali, Abdallah El; Lushnikova, Alina; Alavi, Hamed; Rintel, Sean; Kun, Andrew L; Shaer, Orit; et al. (CHI 2023, 2023)
The COVID-19 pandemic led to a sudden shift to virtual work and events, with the last two years enabling an appropriated and rather simulated togetherness—the hybrid mode. As we return to in-person events, it is important to reflect on not only what we learned about technologies and social justice, but about the types of events we desire, and how to re-design them accordingly. This SIG aims to reflect on hybrid events and their execution: scaling them across sectors, communities, and industries; considering trade-offs when choosing technologies; studying best practices and defining measures of “success” for hybrid events; and finally, identifying and charting the wider social, ethical, and legal implications of hybrid formats. This SIG will consolidate these topics by inviting participants to collaboratively reflect on previous hybrid experiences and what can be learned from them.
SIGCHI Event